2021
DOI: 10.1007/s00261-021-03351-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal fibrosis in patients with chronic kidney disease by shear wave elastography: a comparative analysis with pathological findings

Abstract: Purpose To explore the elastic values obtained by shear wave elastography (SWE) in assessing renal fibrosis in chronic kidney disease (CKD). Methods One hundred and twenty-four patients with CKD who underwent renal biopsy were prospectively enrolled between April 2019 and June 2021. SWE was performed to measure the renal cortex stiffness, presented as SWE parameters, including the minimum, mean, and maximum elasticity (namely Emin, Emean, and Emax). Then, the patients with different kidney pathological impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Some scholars [ 23 ] only explored the positive predictive value and accuracy of CT in the diagnosis of CKD in their studies, while the related diagnostic data obtained in this study were more comprehensive, making it one of the strengths of this study. The study results confirmed that in the clinical diagnosis of CKD at different stages, the AUC value, sensitivity, specificity, and other indicators of 640-slice volume CT were higher than those of CDFQ diagnosis, and the reason might be that 640-slice volume CT scan is an imaging diagnostic technique that integrates anatomy and function, which can accomplish the “one-stop” evaluation of organs, greatly improve the temporal and spatial resolution, also ensure the image definition, and without the need for increasing the amount of additional radiation dose and contrast agent, complete comprehensive evaluation of renal function, presenting its value for the diagnosis and treatment of CKD; whereas, the results of CDFQ are greatly related to the skill of the examining physician, which combined with its image definition and resolution lower than 640-slice volume CT, results in limitations in diagnosis [ 24 , 25 ]. The contributions of the study were as follows: it aimed to provide a well-established and efficient diagnostic scheme for patients and the basis for developing a precise clinical treatment plan by implementing CDFQ versus CT diagnosis for CKD patients and comparing imaging indexes of patients at all stages, which is a great advance and development of clinical imaging diagnosis, has a broad guidance in modern diagnosis of renal diseases, and is undoubtedly a future direction of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars [ 23 ] only explored the positive predictive value and accuracy of CT in the diagnosis of CKD in their studies, while the related diagnostic data obtained in this study were more comprehensive, making it one of the strengths of this study. The study results confirmed that in the clinical diagnosis of CKD at different stages, the AUC value, sensitivity, specificity, and other indicators of 640-slice volume CT were higher than those of CDFQ diagnosis, and the reason might be that 640-slice volume CT scan is an imaging diagnostic technique that integrates anatomy and function, which can accomplish the “one-stop” evaluation of organs, greatly improve the temporal and spatial resolution, also ensure the image definition, and without the need for increasing the amount of additional radiation dose and contrast agent, complete comprehensive evaluation of renal function, presenting its value for the diagnosis and treatment of CKD; whereas, the results of CDFQ are greatly related to the skill of the examining physician, which combined with its image definition and resolution lower than 640-slice volume CT, results in limitations in diagnosis [ 24 , 25 ]. The contributions of the study were as follows: it aimed to provide a well-established and efficient diagnostic scheme for patients and the basis for developing a precise clinical treatment plan by implementing CDFQ versus CT diagnosis for CKD patients and comparing imaging indexes of patients at all stages, which is a great advance and development of clinical imaging diagnosis, has a broad guidance in modern diagnosis of renal diseases, and is undoubtedly a future direction of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that structural and functional changes in the kidneys of diabetic nephropathy patients can be evaluated with SWE 24 . There are studies that have determined that SWE values decrease in the late stages of chronic kidney disease, in which it has been concluded that in addition to fibrosis, kidney stiffness is affected by perfusion changes 13,25 . In a study by Leong et al, it was claimed that the increase in kidney stiffness was related to glomerular sclerosis and interstitial fibrosis rather than vascular sclerosis 14 .…”
Section: Di̇scussionmentioning
confidence: 99%
“…24 There are studies that have determined that SWE values decrease in the late stages of chronic kidney disease, in which it has been concluded that in addition to fibrosis, kidney stiffness is affected by perfusion changes. 13,25 In a study by Leong et al, it was claimed that the increase in kidney stiffness was related to glomerular sclerosis and interstitial fibrosis rather than vascular sclerosis. 14 In a study of patients with IgA nephropathy, it was determined that although SWE values increase with interstitial fibrosis and the degree of tubular atrophy, a statistically significant difference was determined between the SWE values and interstitial fibrosis.…”
Section: _ Iscussionmentioning
confidence: 99%
See 2 more Smart Citations